Effects of Infectious Diseases on Population Dynamics of Marine Organisms in Chesapeake Bay - Jerelle A. Jesse; M. Victoria Agnew; Kohma Arai; C. Taylor Armstrong; Shannon M. Hood; Mariah L. Kachmar; Jessie T. Long; Alexandra J. McCarty; Morgan O. Ross; Kasondra D. Rubalcava; Jacob Shaner; Sakura Tanaka; et al. (Estuaries and Coasts, 2021)
Diseases are important drivers of population and ecosystem dynamics. This review synthesizes the effects of infectious diseases on the population dynamics of nine species of marine organisms in the Chesapeake Bay. Diseases generally caused increases in mortality and decreases in growth and reproduction. Effects of diseases on eastern oyster ( Crassostrea virginica ) appear to be low in the 2000s compared to effects in the 1980s–1990s. However, the effects of disease were not well monitored for most of the diseases in marine organisms of the Chesapeake Bay, and few studies considered effects on growth and reproduction. Climate change and other anthropogenic effects are expected to alter host-pathogen dynamics, with diseases of some species expected to worsen under predicted future conditions (e.g., increased temperature). Additional study of disease prevalence, drivers of disease, and effects on population dynamics could improve fisheries management and forecasting of climate change effects on marine organisms in the Chesapeake Bay.